021 Non-standard practice of phlebotomy techniques: a significant cause of wasted samples and potential misleading results in Emergency Medicine. (14th September 2011) - Berg, J E; Berg, J D; Ahee, P
Abstract : Objectives and Backgrounds: Phlebotomy is a potential cause of pre-analytical errors in the setting of a busy Emergency Department. We have studied current phlebotomy techniques in the Majors area comparing these to standard protocols that should be followed. We have looked at the incidence of haemolysed samples and compared this with that seen in the wider hospital. Methods: Phlebotomy episodes (n=50) were observed and compared to standard procedures. A computer based search of the number of haemolysed samples from Emergency Medicine and all hospital in-patients was reviewed. Results: A total of 13 different types of Emergency Department staff were observed undertaking 50 phlebotomy episodes in the Majors area of the Emergency Department. Four different ways of taking blood were observed; cannulation and a syringe (38%), cannula with evacuated tube and adaptor (42%), syringe and needle into vein (14%), evacuated tube system used conventionally (6%). Where a syringe was used, two methods of transfer into the sample tube were observed; needle kept on with cap piercing (77%) and needle and evacuated cap both removed (23%). On 20 out of 50 phlebotomy episodes (40%), the potassium EDTA tube was filled prior to the biochemistry tube. A study of ward based phlebotomy found 30 of 1034 samples were haemolysed (2.9%). In the 50 phlebotomy episodes in the Majors area of the Emergency Department 24% produced a haemolysed sample (p<0.0001). Study of the samples taken from all areas of Emergency Medicine over a 7-day period showed 52 of 485 were haemolysed (10.7%; p<0.0001). Conclusions: Our results show that phlebotomy techniques in the Emergency Department vary considerably to those set out in standard protocols and manufacturers' guidelines. The evacuated tube system was used incorrectly over 50% of the time. In particular our results suggest that the use of small lumen cannula in the Majors area is a significant cause of haemolysed samples. Most staff were clearly unaware of the importance of the order of sample draw, which can lead to incorrect results for important analytes such as potassium, calcium and magnesium. There is also likely to be an increased incidence of needle stick injuries with samples being stabbed into collection tubes. Addressing these issues will help improve performance in hard times.